LEMBAH BESOA: TEKTONIK DAN SITUS (Besoa Valley: Tectonics and Sites) - Intan, Muh. Fadhlan S. (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2018)
Besoa Valley (Poso, Central Sulawesi) has a lot of remains of megalithic culture, which has not been considered by environmental researchers, especially geoarchaeology. Thus, it is necessary to do surface geological mapping in general as one of the efforts to present geological information related to the Besoa Valley Megalithic site. The aim is to find out the geomorphological, stratigraphic and geological structures in the region. Research methods are carried out through literature review, surveys, field data analysis and interpretation. Environmental observations provide information about morphology, constituent rocks, and geological structures of the Besoa Valley. There are ten megalithic sites in the Besoa Valley. Tectonic activities and geological structures that trigger natural disasters are nine elements, one of which is the Palu-Koro Fault. The quite active tectonic plate shift in the Palu-Koro Fault, making the Megalithic region of the Besoa Valley, is prone to earthquakes. Geoarchaeological research in the Besoa Valley, will provide benefits in the knowledge of human wisdom at that time, in an effort to adapt to the conditions of the surrounding natural environment, where the Besoa Valley is an integral part of the Palu-Koro Fault.ABSTRAKLembah Besoa (Poso, Sulawesi Tengah) banyak menyimpan tinggalan budaya megalitik, yang selama ini belum diperhatikan oleh peneliti lingkungan, khususnya geoarkeologi. Dengan demikian, perlu dilakukan pemetaan geologi permukaan secara umum sebagai salah satu upaya menyajikan informasi geologi terkait dengan situs Megalitik Lembah Besoa. Tujuannya adalah untuk mengetahui aspek-aspek geomorfologi, stratigrafi dan struktur geologi di wilayah tersebut. Metode penelitian dilakukan melalui kajian pustaka, survei, analisis data lapangan dan interpretasi. Pengamatan lingkungan memberikan informasi tentang morfologi, batuan penyusun, dan stuktur geologi Lembah Besoa. Terdapat sepuluh situs megalitik di Lembah Besoa. Kegiatan tektonik dan struktur geologi yang memicu terjadinya bencana alam ada sembilan unsur, salah satunya adalah Patahan Palu-Koro. Pergeseran lempeng tektonik yang cukup aktif di Sesar Palu-Koro, membuat wilayah Megalitik Lembah Besoa, rawan terhadap gempa bumi. Penelitian geoarkeologi di Lembah Besoa, akan memberikan manfaat dalam pengetahuan tentang kearifan manusia pada masa itu, dalam upaya menyesuaikan diri dengan kondisi lingkungan alam sekitarnya, dimana Lembah Besoa merupakan bagian yang tak terpisahkan dari Patahan Palu- Koro.